Management Risks In Financing Murabahah At BMT PT. South Kalimantan Regional Development Bank - Firdaus, Firdaus (Jurnal Ekonomi, 2024)
There are several problems and risks that occur in financing at BMT PT. South Kalimantan Regional Development Bank. The risks that occur at BMT PT. The South Kalimantan Regional Development Bank has bad credit, which is a risk resulting from members' failure to pay financing installments. This risk arises because most members' income has decreased due to market stands being empty of customers. The focus of this research is on how to apply risk management in financing as well as the causes and solutions. The research method used is a qualitative approach and uses a case study strategy. Then the data collection was carried out by connecting questions from the data obtained with conclusions from interviews with several parties from BMT PT. South Kalimantan Regional Development Bank. Apart from the risks that occur in murabahah financing, the research results also explain the analysis practiced by BMT PT. South Kalimantan Regional Development Bank to minimize risks with the 5C principles which cannot be separated from Sharia principles. The efforts made by BMT PT. The South Kalimantan Regional Development Bank in facing the risk of problematic financing is by approaching, rescheduling, reconditioning, restructuring and creating a collection group.